Attitudes and purchase intention towards eco-friendly products among Nepalese youth - Ghimire, Santosh Kumar (International Journal of Operational Research/Nepal, 2020)
This research study aimed to examine the green purchase attitudes of Nepalese youths. Due to the rapid technological changes the environment may be affected positively or negatively. This research is conducted to identify factors affecting the young Nepalese consumers’ intention in purchasing eco-friendly products and targeted on the youths with the age ranging from 18 to 35 years. Therefore, there are two independent variables identified in this research project that could affect youth consumer attitude toward intention to purchase green products. These include the attitudes toward environmental protection and knowledge & awareness of eco-friendly products whereas the other variables such as eco labels, educational level and the experience had been identified as the intervening variables all of which had the major impact on the green purchase intention (GPI). Primary data were collected through the questionnaire in order to inspect the research objectives. In total 115 responses were collected and the reliability test, descriptive analysis, hypothesis test and Pearson correlation analysis are carried out. Consequently, this study carried out to determine the significance of contributing youth attitudes toward intention to purchase green products in Nepalese scenario.